Adherence to self-monitoring healthy lifestyle behaviours through mobile phone-based ecological momentary assessments and photographic food records over 6 months in mostly ethnic minority mothers. Issue 4 (4th December 2017) - Comulada, W Scott; Swendeman, Dallas; Koussa, Maryann K; Mindry, Deborah; Medich, Melissa; Estrin, Deborah; Mercer, Neil; Ramanathan, Nithya
Abstract: Objective: Mobile phones can replace traditional self-monitoring tools through cell phone-based ecological momentary assessment (CEMA) of lifestyle behaviours and camera phone-based images of meals, i.e. photographic food records (PFR). Adherence to mobile self-monitoring needs to be evaluated in real-world treatment settings. Towards this goal, we examine CEMA and PFR adherence to the use of a mobile app designed to help mothers self-monitor lifestyle behaviours and stress. Design/Setting: In 2012, forty-two mothers recorded CEMA of diet quality, exercise, sleep, stress and mood four times daily and PFR during meals over 6 months in Los Angeles, California, USA. Subjects: A purposive sample of mothers from mixed ethnicities. Results: Adherence to recording CEMA at least once daily was higher compared with recording PFR at least once daily over the study period (74 v . 11 %); adherence to both types of reports decreased over time. Participants who recorded PFR for more than a day ( n 31) were more likely to be obese v . normal- to overweight and to have higher blood pressure, on average (all P <0·05). Based on random-effects regression, CEMA and PFR adherence was highest during weekdays (both P <0·01). Additionally, PFR adherence was associated with older age ( P =0·04). CEMA adherence was highest in the morning ( P <0·01). PFR recordings occurred throughout the day. Conclusions: Variations in population and temporal characteristics should be considered for mobile assessment schedules. Neither CEMA nor PFR alone is ideal over extended periods.